The social assimilation of immigrants - Domenico de Palo; Riccardo Faini; Alessandra Venturini (Institute for the Study of Labor (IZA), 2006)
Policy makers in migrant-receiving countries must often strike a delicate balance between economic needs, that would dictate a substantial increase in the number of foreign workers, and political and electoral imperatives, that typically result in highly restrictive immigration policies. Promoting integration of migrants into the host country would go a long way in alleviating the trade off between economic and political considerations. While there is a large literature on the economic assimilation of immigrants, somewhat less attention has been devoted to other - and equally crucial - dimensions of migrants' integration, namely the process of social assimilation. The aim of this paper is to take a close look at migrants' social integration into the host country. We rely on the European Community Household panel (ECHP), which devotes a full module to the role and relevance of social relations for both migrants and natives. An innovative feature of this analysis is that it relies on migrants perceptions about their integration rather than as is typically the case in most opinion surveys on natives attitudes toward migrants. The main results of the paper can be summarized as follows. First, migrants particularly from non EU origins - are at a disadvantage in the fields of social relations. Even after controlling for their individual characteristics, such as age, education, family size, and employment status, they tend to socialize less than natives. Second, migrants tend to converge, albeit quite slowly, to the standard of natives. This finding highlights the risks of short term migration, where migrants tend to be constantly marginalized. Third, education has a significant impact on the type of social activities that individuals undertake. More educated people tend to relate somewhat less with their close neighbourhood, but quite intensively with the broader community. The implication for policy makers concerned about the creation of ethnic enclaves is to promote education among immigrants' community.
urn:nbn:de:101:1-2008071766
Keywords: 330